Beyond small lot subdivision: towards municipality-initiated and resident-supported precinct scale medium density residential infill regeneration in greyfield suburbs. Issue 4 (1st October 2020) - Newton, Peter; Glackin, Stephen; Witheridge, Jennifer; Garner, Lisa
ABSTRACT: Land supply for new housing in the established middle-suburbs (greyfields), where much urban infill potential exists, is "locked up" due to restrictive land-use regulation. As a result, most residential infill is occurring as fragmented, sub-optimal small lot subdivision. This paper outlines critical aspects in implementing a new development model – greyfield precinct renewal – which requires transformative change in municipal strategic planning, new zoning development schemes, innovative medium-density dwelling designs, and clusters of property-owners who can be motivated to capitalise on lot-consolidation value-uplift to overcome the negative externalities of small lot, fragmented, infill.